Kandungan Protein Kecap Nira Lontar dengan Variasi Konsentrasi Tepung Tempe - Ledo, Mellissa Erlyn Stephanie (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2020)
Soy sauce is generally made from soybeans. However, palm oil has the potential to be used as an ingredient in soy sauce which can be combined with tempeh flour. This study aims to assess the protein content of lontar juice with variations in the concentration of tempeh flour. The research method used in this study was an experimental method with a completely randomized design (CRD) factorial, with the treatment of tempeh flour concentrations of 0%, 3%, 5%, 7%, 10%. The results showed that the treatment with the addition of 10% tempeh flour gave the product with the highest protein content compared to other treatments, namely 4.90%. In addition, the organoleptic test of soy sauce which includes color, aroma, taste, and viscosity in the addition of 10% tempeh flour showed the best results.